2019
DOI: 10.1155/2019/1315047
|View full text |Cite
|
Sign up to set email alerts
|

An API Semantics-Aware Malware Detection Method Based on Deep Learning

Abstract: The explosive growth of malware variants poses a continuously and deeply evolving challenge to information security. Traditional malware detection methods require a lot of manpower. However, machine learning has played an important role on malware classification and detection, and it is easily spoofed by malware disguising to be benign software by employing self-protection techniques, which leads to poor performance for existing techniques based on the machine learning method. In this paper, we analyze the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A deep learning-based ensemble learning detection framework was introduced by Ma, et al (2019) for API fragments [22], but the malware detection accuracy was not improved. Xiao, et al ( 2019) developed a novel behavior-based deep learning framework (BDLF) to classify the malware attack and increase the precision [23].…”
Section: Related Workmentioning
confidence: 99%
“…A deep learning-based ensemble learning detection framework was introduced by Ma, et al (2019) for API fragments [22], but the malware detection accuracy was not improved. Xiao, et al ( 2019) developed a novel behavior-based deep learning framework (BDLF) to classify the malware attack and increase the precision [23].…”
Section: Related Workmentioning
confidence: 99%
“…The results of experiments showed that both approaches worked well, and the framework combined two models had a better performance, which had an accuracy of 96.7% in classification. Ma et al [38] analyzed malicious malware and designed a detection framework based on API fragments. The framework utilized sliding window operation to split API sequences into an Nlength API fragment.…”
Section: Related Work a Api Based Malware Detectionmentioning
confidence: 99%
“…ere are also other machine learning methods to learn the features. Ma et al [19] analyze the local maliciousness about malware and implements an anti-interference detection framework based on API fragments, which can effectively detect malware. Anderson and Roth [20] offer a public labeled benchmark dataset for training machine learning models to statically detect malicious PE files.…”
Section: Related Workmentioning
confidence: 99%